Being Young and Muslim: New Cultural Politics in the Global South and North (Religion and Global Politics Series) by Linda Herrera and Asef Baya, eds. (New York: Oxford University Press, 2010. pbk. 426 pages) (American Journal of Islam and Society, 2011)
Being Young and Muslim is a compilation of narratives that address thecultural politics of Muslim youth from multiple perspectives—youthfullifestyles, rebellion, and accommodations signify the “intricate relationshipbetween the young, youth identities and Islam” (19). The volume isdivided into five parts. Each part contains several chapters and contextualizesan aspect associated with being young and Muslim. Most of the chaptersin this volume were produced for two international workshops on the“Making of the Muslim Youth” that were presented in Leiden in February2005 and in The Hague in October 2006 (v). In the first chapter “Introduction:Being Young and Muslim in Neoliberal Times,” Linda Herrera andAsef Bayat present the focal points to be addressed throughout the volume:the approaches and directions Muslim youth will undertake in an era with“multiple constraints and opportunities of being young, Muslim, marginalized,and subjects of social control” (11) ...